Make a Lab - A Project Focused on the Gender Gap in STEM Fields - Vasconcelos, Veronica; Bigotte, Emilia; Marques, Luis; Almeida, Ricardo (Proceedings of the International Conference on European Association for Education in Electrical and Information Engineering, 2022)
STEM graduates play a key role in the society's sustainable development, contributing to the productivity, competitiveness and progress of the economy. However, the number of students enrolled in STEM courses is low, despite the high demand and valuation by the labour market. This reality is even more striking when analysing the numbers related to the presence of women in STEM fields, particularly in engineering courses. The under-representation of women is a problem arising from multiple factors that need to be overcome through educational policies and specific initiatives. This article describes the iProg, Scratch on Road, and Scratch4All projects that aimed at the development of competences in technological areas, namely in programming and robotics, among students from basic schools. The positive impacts of the mentioned projects encouraged the authors to create the Make a Lab project, a partnership between Coimbra Institute of Engineering (ISEC) and CASPAE, a Private Social Solidarity Institution. The central goal of this project is to respond to the critical gender gap in STEM subjects, having as a goal that 70% of the students involved in the program activities should be women. This project aims to promote interest in science and technology in students from secondary schools through the use of creative, experimental and exploratory approaches. The development of technological products adopt project based learning methodologies, mainly implemented in a laboratory located at ISEC campus. The co-definition and co-creation of these products is based on a mentoring process carried out by ISEC students, preferably women. One-off initiatives will also be carried out, as for instance hands-on experiences and thematic workshops. An itinerant exhibition will be organized using the technological products developed over the Make a Lab project. The exhibition will be available to basic and secondary schools, after the terminus of the project.